Proyeksi Sosial Kebijakan Pemerataan Pembangunan Pendidikan dalam Progres Data Nasional Perspektif Sosiologi - Masduki, Hendri; Basri, La; Surahman, Fajar (Universitas Muhammadiyah Sorong, 2023)
The social projection of policies for equitable educational development in the progress of national data is the focus of the study in the research activities carried out in this writing. The research includes descriptive research with evaluative methods. The results of an in-depth discussion of research findings with a theoretical basis show that the social projection of policies for equitable educational development in the progress of national data from a sociological perspective as an entity related to the social system and social solidarity which is a model of synergy between the state and society in order to mobilize; accommodate; accommodate; effort; and shared responsibility in accelerating the achievement of equitable educational development within the framework of the diversity of the Indonesian national and state system.